Supplementary data: Chemoradiotherapy in octogenarians as primary treatment for muscle-invasive bladder cancer - McPherson, Victor A.; Rodrigues, George; Bauman, Glenn; Winquist, Eric; Chin, Joseph; Izawa, Jonathan; Potvin, Kylea; Ernst, Scott; Venkatesan, Varagur; Sexton, Tracy; Ahmad, Belal; Power, Nicholas (Canadian Urological Association Journal, 2017)
N/A